2020
DOI: 10.1021/acs.joc.0c02246
|View full text |Cite
|
Sign up to set email alerts
|

Boron Lewis Acid-Catalyzed Hydrophosphinylation of N-Heteroaryl-Substituted Alkenes with Secondary Phosphine Oxides

Abstract: We report the boron-catalyzed hydrophosphinylation of N-heteroaryl-substituted alkenes with secondary phosphine oxides that furnishes various phosphorus-containing N-heterocycles. This process proceeds under mild conditions and enables the introduction of a phosphorus atom into multisubstituted alkenylazaarenes. The available mechanistic data can be explained by a reaction pathway wherein the C–P bond is created by the reaction between the activated alkene (by coordination to a boron catalyst) and the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Based on the insights gained from the H/D experiments, we applied boron Lewis acid catalyzed conditions for the P-H addition of diethyl phosphite (1a) to pyridyl alkene 2a (Table 1). 12 The hydrophosphorylated product, -pyridyl phosphonate 3aa, was formed in 92% yield in toluene at 40 °C after 16 hours when catalyzed by 20% B(C 6 F 5 ) 3 (Table 1, entry 1), while <5% yield of 3aa was obtained in the absence of the catalyst (entry 2). The reaction with lower catalyst loadings led to a significant decrease in the yield of 3aa (entry 3).…”
Section: Equation 1 Cooperative Deprotonation Of H-phosphonates By La...mentioning
confidence: 99%
“…Based on the insights gained from the H/D experiments, we applied boron Lewis acid catalyzed conditions for the P-H addition of diethyl phosphite (1a) to pyridyl alkene 2a (Table 1). 12 The hydrophosphorylated product, -pyridyl phosphonate 3aa, was formed in 92% yield in toluene at 40 °C after 16 hours when catalyzed by 20% B(C 6 F 5 ) 3 (Table 1, entry 1), while <5% yield of 3aa was obtained in the absence of the catalyst (entry 2). The reaction with lower catalyst loadings led to a significant decrease in the yield of 3aa (entry 3).…”
Section: Equation 1 Cooperative Deprotonation Of H-phosphonates By La...mentioning
confidence: 99%
“…This protocol could overcome the intrinsic reactivity of anilines and provide a new strategy to afford the β-phosphoryl enamine motif. However, the preparation of aminophosphinoylated maleimides using the above-mentioned transformation is extremely challenging, mainly due to the well-developed and incidental copper-catalyzed oxidative dehydrogenation coupling of anilines to lead to aromatic azo compounds, 8 hydrophosphinylation of H-phosphonates with electron-deficient alkenes, 9 oxidative N–P cross-coupling between H-phosphonates and anilines, 10 and homo-dehydrogenative P–P and P–O–P coupling of H-phosphonates. 11…”
Section: Introductionmentioning
confidence: 99%
“…Although some methods for catalyzing olefins to construct PÀ C bonds have been developed, they are mainly carried out under the conditions of transition metals, [15][16][17][18][19] free radical initiators such as AIBN, [20,21] ionic conditions [22] or Lewis acids [23] as shown in Scheme 1. For example, in 2002, Montchamp and Deprèle reported various palladium catalysts could promote the addition of hypophosphorous derivatives ROP(O)H 2 to alkenes and alkynes in good yields under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[22] In 2020, Lee et al reported the boron-catalyzed hydrophosphorylation of N-heteroaryl-substituted alkenes with secondary phosphine oxides that furnished various phosphoruscontaining N-heterocycles. [23] Thus, it can be seen that the above methods still require complicated reaction conditions, and most of the products focused on tetracoordinate PÀ C bonds. Accordingly, it is still significant to develop a simple method to form PÀ C bonds at room temperature and without a metal catalyst.…”
Section: Introductionmentioning
confidence: 99%